Faith in the Unexpected: The Event of Obligation in Teaching (LEARNing Landscapes, 2021)
In the face of standardization and rationalization, the language of the expected, the predictable and the planned has enveloped teaching and teacher education worldwide. However, in a recent study about the emotional toll of teaching in two Canadian provinces, teachers’ stories overflowed with allusions to the unexpected, the unplanned, and the unforeseeable. We explore those stories, and in the company of John Caputo’s writing about teaching and ethics, we speculate what they suggest about a life lived in teaching. We posit that obligation is the insistent ghost that haunts teaching in the midst of the machinery of schooling.
Keywords: teaching; obligation; weak ethics; teachers' lives